Predation by Geoffroy's cat on ferruginous Pygmy-Owl in Caldén semiarid forest, Argentina - Santillán, Miguel Ángel (2014)
The Ferruginous Pygmy-Owl (Glaucidium brasilianum) has a broad geographic distribution, occurring from the southwestern United States to Central America and South America (Holt et al. 1999, Proudfoot and Johnson 2000).